2014
DOI: 10.1155/2014/465178
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Forces in Micromilling of Hardened AISI H13 Steel with Different Grain Sizes Using the Taguchi Methodology

Abstract: The micromachining process has been applied to the free form and micromolds markets. This has occurred due to the growth in demand for microcomponents. However, micromachining of hardened steels is a challenge due to the reduction in tool life and the increase of the surface roughness when compared with the macromachining process. This paper focused on the analysis of micromilling forces on hardened AISI H13 steel with different grain sizes. Experimental tests were carried out on workpieces with different aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Based on literature sources, mentioned cutting edge radius is very significant factor. Increase of mentioned radius causes phenomena of size effect and related negative phenomena which is not found in machining on macro level [20].…”
Section: Discussionmentioning
confidence: 98%
“…Based on literature sources, mentioned cutting edge radius is very significant factor. Increase of mentioned radius causes phenomena of size effect and related negative phenomena which is not found in machining on macro level [20].…”
Section: Discussionmentioning
confidence: 98%
“…Micro-milling is a precise and flexible technology to manufacture complex 3D geometries in various types of materials (metals and its alloys, polymers, ceramics, graphite, composites etc. [3,[26][27][28][29][30][31][32][33][34][35][36][37][38]) by relatively high material removal rates. The kinematic of micro-milling is similar to the conventionalsized milling process; however, there are some unique phenomena and key issues: (i) the size of the cutting tool can be extremely small (diameter of 25 μm [39] or 50 μm [40]), the length-to-diameter ratio is therefore often high.…”
Section: Micro-milling Processmentioning
confidence: 99%
“…Micro-machining researches are carried out in a wide range of materials, with a very significant proportion of the research being steels, which is the most widely used metal in the engineering world. For the sake of example, many researchers studied micro-machinability of AISI 1045 (partly as reference material) [4,38,46,77,88], different stainless steels [43,84,114], and also hardened steels [29,30,84,157]. Several researchers have also investigated aluminium micromachining [95,109,125,142].…”
Section: Micro-milled Workpiece Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauro et al 29 conducted experimental trials to assess micro-milling forces when machining hardened steel with different grain sizes. It was found that feed rate was the most significant factors affecting the cutting force, that is, large grain sizes led to lower cutting forces.…”
Section: Materials Microstructure Effectmentioning
confidence: 99%